321 new multi-purpose barley genotypes for food, feed, forage, and malt shared with National Agricultural Research Systems (NARS) partners and collaborators for final evaluation and potential release - CGIAR Research Program on Livestock (2020)
The elite genotypes have been shared with NARS, private seed sector and academic for research, breeding and potential variety release